Fostering open collaboration in drug development for paediatric brain tumours. (24th September 2019) - Wong, Jong Fu; Brown, Elizabeth J.; Williams, Eleanor; Bullock, Alex N.
Abstract: Brain tumours have become the leading cause of child mortality from cancer. Indeed, aggressive brainstem tumours, such as diffuse intrinsic pontine glioma (DIPG), are nearly uniformly fatal. These tumours display a unique set of driver mutations that distinguish them from adult gliomas and define new opportunity for the development of precision medicines. The specific association of ACVR1 mutations with DIPG tumours suggests a direct link to neurodevelopment and highlights the encoded bone morphogenetic protein receptor kinase ALK2 as a promising drug target. Beneficial effects of ALK2 inhibition have now been observed in two different in vivo models of DIPG. Nonetheless, such tumours present a huge challenge for traditional economic models of drug development due to their small market size, high failure rate, tumour location and paediatric population. Moreover, a toolkit of different investigational drugs may be needed to fully address the heterogeneity of these tumours in clinical trials. One new business model is suggested by M4K Pharma, a recent virtual start up that aims to align diffuse academic and industry research into a collaborative open science drug discovery programme. Fostering scientific collaboration may offer hope in rare conditions of dire unmet clinical need and provide an alternative route to affordable medicines.